Restoration of Mitochondrial Integrity, Telomere Length, and Sensitivity to Oxidation by In Vitro Culture of Fuchs' Endothelial Corneal Dystrophy Cells - Gendron, Sébastien P.; Thériault, Mathieu; Proulx, Stéphanie; Brunette, Isabelle; Rochette, Patrick J. (Investigative ophthalmology & visual science, 2016)
Fuchs' endothelial corneal dystrophy (FECD), a degenerative disease of the corneal endothelium that leads to vision loss, is a leading cause of corneal transplantation. The cause of this disease is still unknown, but the implication of oxidative stress is strongly suggested. In this study, we analyzed the impact of FECD on mitochondrial DNA (mtDNA) integrity and telomere length, both of which are affected by the oxidative status of the cell. We compared the levels of total mtDNA, mtDNA common deletion (4977 bp), and relative telomere length in the corneal endothelial cells of fresh Descemet's membrane-endothelium explants and cultured cells from healthy and late stage FECD subjects. Oxidant-antioxidant gene expression and sensitivity to ultraviolet A (UVA)- and H2O2-induced cell death were assessed in cultured cells. Our results revealed increased mtDNA levels and telomere shortening in FECD explants. We also found that cell culture restores a normal phenotype in terms of mtDNA levels, telomere length, oxidant-antioxidant gene expression balance, and sensitivity to oxidative stress-induced cell death in the FECD cells compared with the healthy cells. Taken together, these results bring new evidence of the implication of oxidative stress in FECD. They also show that FECD does not evenly affect the integrity of corneal endothelial cells and that cell culture can rehabilitate the molecular phenotypes related to oxidative stress by selecting the more functional FECD cells.